2023
DOI: 10.1071/sr23102
|View full text |Cite
|
Sign up to set email alerts
|

Long-term effects of olive mill waste waters spreading on the soil rhizospheric properties of olive trees grown under Mediterranean arid climate

Siwar Abdennbi,
Mohamed Chaieb,
Ali Mekki

Abstract: Context The spreading of olive mill waste waters (OMWW) could offer an appropriate management option to add value to this agricultural by-product, such as to increase soil fertility and plant productivity. Aims The main objective of this work was to evaluate the effects of the application of OMWW (at a fixed dose of 50 m3 ha−1), in the long term (20 years) on the soil rhizospheric properties and on old olive trees (80 years old) growth and productivity. Methods The experimental site consists of f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 125 publications
0
1
0
Order By: Relevance
“…The enumeration of the total flora 3 months after spreading revealed that the addition of OMWW is accompanied by an increase in the number of microorganisms in the soil compared to the control [10], (Figure 3). This increase depends on the dose provided and is remarkable for the two superficial layers going from the surface to 40cm depth.…”
Section: Effect Of Spreading Omww On Soil Microfloramentioning
confidence: 98%
“…The enumeration of the total flora 3 months after spreading revealed that the addition of OMWW is accompanied by an increase in the number of microorganisms in the soil compared to the control [10], (Figure 3). This increase depends on the dose provided and is remarkable for the two superficial layers going from the surface to 40cm depth.…”
Section: Effect Of Spreading Omww On Soil Microfloramentioning
confidence: 98%